Tidwell, C., & Soles, C. (Eds). (2021). Fear and Nature: Ecohorror Studies in the Anthropocene - Rahaman, Tohidur (Journal of Ecohumanism, 2022)
Tidwell, C., & Soles, C. (Eds). (2021). Fear and Nature: Ecohorror Studies in the Anthropocene. Penn State University Press. ISBN: 9780271090214